Exploring the Anti-Acne Potential of Impepho [Helichrysum odoratissimum (L.) Sweet] to Combat Cutibacterium acnes Virulence - De Canha, Marco Nuno; Komarnytsky, Slavko; Langhansova, Lenka; Lall, Namrita (Frontiers in Pharmacology, 2020)
The Gram-positive bacterium Cutibacterium acnes (previously Propionibacterium acnes), plays an important role in the pathogenesis and progression of the dermatological skin disorder acne vulgaris. The methanolic extract of Helichrysum odoratissimum (HO-MeOH) was investigated for its ability to target bacterial growth and pathogenic virulence factors associated with acne progression. The GC-MS analysis of HO-MeOH identified α-humulene, α-curcumene and carophyllene as major constituents, which correlated with previous reports. The HO-MeOH extract exhibited potent antimicrobial activity against C. acnes (ATCC 6919) with an MIC of 7.81 µg/ml. It enhanced the antimicrobial activity of benzoyl peroxide (BPO). The extract showed high specificity against C. acnes cell aggregation at sub-inhibitory concentrations, preventing biofilm formation. Mature C. acnes biofilms were disrupted at a sub-inhibitory concentration of 3.91 µg/ml. At 100 µg/ml, HO-MeOH reduced IL-1α cytokine levels in C. acnes-induced human keratinocytes (HaCaT) by 11.08 %, highlighting its potential as a comedolytic agent for the treatment of comedonal acne. The extract exhibited an IC50 of 157.50 µg/ml against lipase enzyme activity, an enzyme responsible for sebum degradation, ultimately causing inflammation. The extract’s anti-inflammatory activity was tested against various targets associated with inflammatory activation by the bacterium. The extract inhibited pro-inflammatory cytokine levels of IL-8 by 48.31 % when compared to C. acnes-induced HaCaT cells at 7.81 µg/ml. It exhibited cyclooxygenase-II (COX-II) enzyme inhibition with an IC50 of 22.87 µg/ml. Intracellular NO was inhibited by 40.39 % at 7.81 µg/ml when compared with NO production in LPS-induced RAW264.7 cells. The intracellular NO inhibition was potentially due to the 2.14 fold reduction of inducible nitric oxide synthase (iNOS) gene expression. The HO-MeOH extract exhibited an IC50 of 145.45 µg/ml against virulent hyaluronidase enzyme activity, which is responsible for hyaluronan degradation and scar formation. This study provides scientific validation for the traditional use of H. odoratissimum as an ointment for pimples, not only due to its ability to control C. acnes proliferation but also due to its inhibitory activity on various targets associated with bacterial virulence leading to acne progression.